Influence of annealing temperature on the magnetic properties of rapidly quenched (Nd,Pr)2-(Fe,Co,Ga,Ti,C)14B/α-Fe nanocomposite ribbons - Sabbaghizadeh, Rahim; Hashim, Mansor; Gholamipour, Reza; Bahmanrokh, Ghazaleh; Shafie, Mohd Shamsul Ezzad (Hindawi Publishing Corporation, 2013)
The effects of different heat treatment temperatures on the structure and magnetic properties of Nd-Fe-B nanocomposite permanent magnetic alloys with nominal composition of Nd9.4Pr0.6Fe74.5Co6B6Ga0.5Ti1.5C1.5 have been investigated. The most practical method to produce nanostructured metallic materials is rapid solidification. Melt spinning with constant wheel speed of V = 40m/s was employed to produce ribbons. As-spun ribbons were examined by using differential scanning calorimetry (DSC) and X-ray diffractometer (XRD) with Cu-kα radiation. The ribbons were annealed at different temperatures in order to extract the best magnetic properties. The XRD and electron microscopy technique results confirm that grains are in the size of less than 50 nm. In addition, optimum magnetic properties were obtained at 700°C annealed temperature.